English and Arabic Language Learning Environments: Islamic Universities Undergraduates' Experiences - Sabani, Nora; Jimmie, Anita; Hasnor, Hanin Naziha (IGI Global, 2020)
The learning environment is defined as “external stimulants” that is exposed or reinforced in learners as a means to challenge their learning experiences. These reinforcements may include physical settings, teaching and learning endeavours, and even cultural and social determiners. This empirical study focuses on the perceived experiences that undergraduates from Brunei, Malaysia, and Indonesia experienced in their Arabic and English language learning environments. This qualitative study employed in-depth interviews with 60 informants that were selected through criterion sampling, snowballing technique. The analysis utilised template analysis. Emerging themes were compared and contrasted, to find similarities and differences. This chapter does not aim to seek the superiority of one learning environment over another but to appreciate the diversity and concord of these institutions. The findings illustrated overlapping, differentiated themes, which included the abovementioned.